Learning Cython Programming. - Herron, Philip (Packt Publishing, 2013)
A practical and a fast-paced guide that gives you all the information you need to start programming using Cython. This book is for developers who love C/C++ for low latency and speed but who also require the ability to add more dynamic features to applications both fast and reliably. It will also show you how you can get new applications off the ground by reusing Python libraries to get started.